Equity in Admissions Policies of Undergraduate Students in Post Democracy in Selected South African Universities - Matsepe, David; Cross, Michael; Fenyane, Samuel (International Journal of Criminology and Sociology, 2022)
This paper investigates the policy pathways that inform and regulate student selection and admission at three selected universities in South Africa, namely the University of the Witwatersrand, the University of Cape Town and the University of KwaZulu-Natal. We argue that these universities have progressed a long way in addressing the race problem in their enrolment strategies. However, their main target group remains students from rich or affluent communities, to the exclusion of potentially good students from marginalised groups, particularly those from under-resourced township and rural schools. As a result, their main challenge in the context of formal access to higher education in South Africa has largely shifted from a race problem to one of social class. This is due to an overemphasis on narrow conceptions of merit that cannot be reconciled with equity and social justice concerns. The paper suggests that current notions of merit warrant reconceptualization in order to embrace these missing dimensions. While there is plenty of evidence that most institutions agree on the need to embrace a particular form of affirmative action to address current social imbalances, given the fierce contestation of redress policies within the South African higher education sector, they find it difficult to develop and implement adequate admission strategies in practice.